Analysis of Culinary Graduates Competency in SMKN 9 Padang Needed by Industry Using NVIVO 11 - Yasmin, Lutfia; Faridah, Anni; Yulastri, Asmar (Universitas Negeri Semarang, 2019)
This study aims to analyze the competence of culinary graduates of SMK Negeri 9 Padang and the competency of graduates expected by the industry. This study uses a qualitative descriptive research method. The research was conducted in three different hotels in the city of Padang, namely Whiz Prime Hotel, Grand Inna Hotel, and Pangeran Beach Hotel. Informants in this study included the culinary industry where graduates worked as well as graduates working in the industry. There are two data collection techniques used, interviews and documentation. Processing data in this study using NVivo 11 software. The results of data analysis showed that there were 17 themes on cognitive aspects, 15 themes on affective aspects, and 18 themes on psychomotor aspects. The results of the analysis of the competence of culinary graduates from SMK Negeri 9 Padang, which is expected by the industry, show that there are 7 themes summarized from cognitive, affective, and psychomotor aspects. In general, the results of the study showed that the cognitive and psychomotor aspects of graduates were good. Cognitive and psychomotor aspects include eating and drinking services, non-alcoholic drinks, pastry, Indonesian food, and continental food. Whereas in the affective aspect an increase is needed, namely the level of self-confidence, adaptation, and discipline.